Reconstruction of Islamic Religious Education Seyyed Hossein Nasr's Perspective - Syamsul Arifin; Amirullah Amirullah; Soleh Amini Yahman; Anip Dwi Saputro (Postgraduate Program Magister Pendidikan Agama Islam, 2022)
This article aims to look at the construction of Islamic education from the perspective of Seyyed Hossein Nasr. Nasr is an Islamic thinker whose capabilities are not in doubt in the study of Islamic philosophy, science, and ethics. The research approach used in this article is a literature review. Research problems are studied and analysed through the literature comprehensively. The results of this study include 1) Seyyed Hossein Nasr's conception of Islamic education which emphasizes human efforts to carry out their duties and obligations as caliphs on earth and servants of Allah; 2) the role of humans as caliphs and servants of Allah can only be obtained with the integrity of the building of science; 3) education construction is carried out through the Islamization of science (science) with a philosophical reformulation of Islamic education in the ontological, epistemological, and axiological domains 4) Islamic education reconstruction is directed at reviewing and rearranging educational goals, characteristics of Islamic educators, characteristics of Islamic students, educational tools, and educational environment.